1994
DOI: 10.1136/bmj.309.6947.86
|View full text |Cite
|
Sign up to set email alerts
|

Pursuit and practice of complementary therapies by cancer patients receiving conventional treatment

Abstract: A sizeable percentage of patients receiving conventional treatments for cancer also use complementary therapies. Patient satisfaction with complementary therapies, other than dietary therapies, was high even without the hoped for anticancer effect. Patients reported psychological benefits such as hope and optimism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
182
9
9

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(236 citation statements)
references
References 7 publications
33
182
9
9
Order By: Relevance
“…Psychological support was once seen as a complementary part to conventional patient care, but now it has been integrated into the process of orthodox treatment, especially for patients suffering from major illnesses such as cancer [41]. Such change might reflect an increasing awareness of the importance of mental health in the population, and this development may have profoundly influenced OM users within the recent decade.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological support was once seen as a complementary part to conventional patient care, but now it has been integrated into the process of orthodox treatment, especially for patients suffering from major illnesses such as cancer [41]. Such change might reflect an increasing awareness of the importance of mental health in the population, and this development may have profoundly influenced OM users within the recent decade.…”
Section: Discussionmentioning
confidence: 99%
“…Those who are better educated are known to be more proactive about their own health in general, particularly preventative measures. 24,25 Kao et al 26 showed in a study of patients undergoing treatment for localised prostate carcinoma that those engaging in alternative therapy practices tended to have higher levels of education and income.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of people with cancer are coming to see the use of complementary therapies as an adjunct to hospital cancer treatment rather than as an alternative approach [1][2][3][4][5]. In this supportive role, complementary therapies are widely used after a cancer diagnosis and in the UK they are included in National Health Service (NHS) guidelines 'Improving Supportive and Palliative Care for Adults with Cancer' [6].…”
Section: Introductionmentioning
confidence: 99%